A magyar-balkáni kapcsolatok egyes dimenziói a 21. század elején - M. Császár, Zsuzsanna (Közép-Európai Közlemények, 2011)
During the Hungarian EU Presidency the Western Balkan has been a priority in the forefont of the Hungarian and European foreign policy. Nowadays we should notice that their is a new, developing subsystem in the Balkan area, where Hungary will be play an important role. Our relationship with the region is identified by the past connections, with other ethnic groups situations (especially on the Serbian-Hungarian relations) and the fact that Hungary could become a facilitator Euro-Atlantic integration, which seems to be the only solution for the region. The task of politics is to create the opportunities in the area of permanent and effective presence, and ensuring the institutions and provide the experience of integration by experts. In the present study, we undertake an analysis of cooperation in different scenes, with particular attention to the economy, which are related to the Western Balkans, such as Serbia, Croatia, Montenegro, Macedonia.